The F-Box Protein Dia2 Regulates DNA Replication - Koepp, Deanna M.; Kile, Andrew C.; Swaminathan, Swarna; Rodriguez-Rivera, Veronica (Molecular biology of the cell, 2006)
Ubiquitin-mediated proteolysis plays a key role in many pathways inside the cell and is particularly important in regulating cell cycle transitions. SCF (Skp1/Cul1/F-box protein) complexes are modular ubiquitin ligases whose specificity is determined by a substrate-binding F-box protein. Dia2 is a Saccharomyces cerevisiae F-box protein previously described to play a role in invasive growth and pheromone response pathways. We find that deletion of DIA2 renders cells cold-sensitive and subject to defects in cell cycle progression, including premature S-phase entry. Consistent with a role in regulating DNA replication, the Dia2 protein binds replication origins. Furthermore, the dia2 mutant accumulates DNA damage in both S and G2/M phases of the cell cycle. These defects are likely a result of the absence of SCF Dia2 activity, as a Dia2 ΔF-box mutant shows similar phenotypes. Interestingly, prolonging G1-phase in dia2 cells prevents the accumulation of DNA damage in S-phase. We propose that Dia2 is an origin-binding protein that plays a role in regulating DNA replication.